The deconstruction of the enemy: Contributions to build peace in Colombia - Ballesteros Guerrero, Elkin Aleixi (2022)
This article presents the results of an investigation where the construction of the enemy was analyzed from educational contexts in Colombia. The methodology used was action research (AR) using interviews that, from the critical discourse analysis (CDA), allowed to evidence some practices and discourses that establish imaginaries about the other being, which in the end helped to understand the need to promote new strategies that allow the deconstruction of these practices that facilitate processes to strengthen the development of peace, achieve greater bonding between family and the educational sphere, and link the social  whenimplementing a pedagogical strategy that favors a culture of stronger peace from the territories.